Gestión Administrativa de inventarios en el Departamento de Bienes, Almacén y Bodega de la Universidad Técnica de Babahoyo - Avila Guerrero, Roger Marcelo (2020)
Within a Department whose responsibility is to manage personal property and manage inventories, storage and its subsequent delivery, it must adopt personnel with good skills to carry out activities correctly, both internally and externally. Safety, weather, weight and other factors that can influence the goods are necessarily important to take into account, since, at the time of handling, they can cause risks that these elements are in poor condition, and even cause accidents. The purpose of this case study is to know the problems that arise in the department, using data collection methodologies to be able to analyze the problem for which the necessary tasks are not carried out, and it is not possible to have efficiency in the administrative management of the goods, knowing the major reasons why the tasks are not carried out correctly. The responses to the methodologies carried out are obtained at the time of conducting the surveys and the interview. The situation in the Department of Goods, Warehouse and Warehouse of the Technical University of Babahoyo has greater relevance in the entrances, exits and storage of goods, so that efficiency is not achieved within the general warehouse, due to the lack of optimization, use and capacity of administrative and logistical resources.